Las categorías de subsunción formal y real en Marx: Una breve aproximación para comprender la universidad en el siglo xxi - Rodríguez, Nelson (2018)
This paper aims to address the study of categories formal and real subsumption from Karl Marx. To this end, a brief historical tour is carried out to support the current affairs of Capital and, based on these categories, to study the current problems of society but in a special way, concentrating the analysis in a particular way on the understanding of the dynamics educational and specialized work. This, with the intention of clarifying the latent logics of subsumption of the university to the conditions of capitalist reproduction and, in addition, the need for transformation of the university institution.